Asuhan Keperawatan Pasien Dengan Isolasi Sosial Di Panti X Jakarta - Solehudin, Solehudin; Nurfadillah, Didah; Iskandar, Maulana; Maulida, Tiara; Maulana, Tio; Syabanasyah, Inas (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Social isolation not only affects the patient's physical appearance, but also impacts his psychological, emotional and social aspects. Nurses have a great responsibility in providing appropriate care and supporting patients during periods of social isolation. The aim of the research is to determine the description of nursing care for clients with social isolation problems. The research used is a Case Study of mental nursing care which consists of assessment, diagnosis, intervention, implementation and evaluation. The assessment includes reasons for admission, predisposing factors, physical examination, psychosocial, mental status, patient's needs for discharge, coping mechanisms, psychosocial and environmental problems, knowledge. Nursing problems: Social isolation, risk of violent behavior, low self-esteem, sensory perception disorders; Auditory and visual hallucinations. The main nursing problem for this client is social isolation. Nursing action plan: Build a relationship of mutual trust by stating the principles of therapeutic communication; Ask the client about the people who live in the same house or room as the client and the people closest to the client. Discuss with the client the causes of social isolation or not wanting to join/associate with other people. Evaluation for a diagnosis of Social Isolation, the client can mention the advantages of interacting with other people and the disadvantages of not interacting with other people, the client can introduce himself and can get to know more than 2 people.